Access-Site Complications in Transfemoral Neuroendovascular Procedures: A Systematic Review of Incidence Rates and Management Strategies. (18th November 2021) - Oneissi, Mazen; Sweid, Ahmad; Tjoumakaris, Stavropoula; Hasan, David; Gooch, M Reid; Rosenwasser, Robert H; Jabbour, Pascal
Graphical Abstract: